Pengaruh Pemberian Jus Jambu Biji Merah terhadap Penurunan Kadar Ldl (Low Density Lipoprotein) dan Kolesterol Total - Junendri Ardian; M. Thonthowi Jauhari; Baiq Fitria Rahmiati (Nutriology : Jurnal Pangan,Gizi,Kesehatan, 2020)
Objective: The purpose of this research is analyzing the influence’s of guava juice intake for LDL’s levels and cholestrol’s total at the age of 40 – 70 years old.Method: Kind of this research is True Experimental researchs with Pre and Post Test Control Group designs. Populations in this research are 20 housewifes with hypercholesterolmia and separated into two groups, the first group is guava juice’s intervention group, and the second is control group with mineral water’s intervention.Results: The result in this research shows that guava juice’s has intake for LDL’s levels and cholestrol’s total at the age of 40 – 70 years old. The test that used for the research is Paired T Test. Cholesterol total levels for guava juice’s intervention has decreased significantly as much as 13,4 mg/dl (with p<0,05) and LDL’s levels has decreased significantly 14,4 mg/dl(with p<0,05). While for the control group cholesterol total levels has increased 6,8 mg/dl but it doen’t mean (with p>0,05) and LDL’s levels has increased too as much as 13,0 mg/dl but it didn’t mean (with p>0,05).Conclusion:Total cholesterol levels in distributioning guava juice decrease significantly 13.4 mg / dl (p <0.05) and LDL levels decreased significantly 14.4 mg / dl (p <0.05). Whereas in the control group total cholesterol levels increased 6.8 mg / dl but were not significant (p> 0.05) and LDL levels increased 13.0 mg / dl but were not significant (p> 0.05).